Exploring the nature and focus of feedback when using video playback in gynecology laparoscopy training - Jena M Hall; Jamie S Pyper (Canadian Medical Education Journal, 2021)
Background: Feedback about intraoperative performance remains a cornerstone of surgical training. Video playback offers one potential method for more effective feedback to surgical residents. More research is needed to better understand this method. This study explores the nature of instructional interactions and feedback in the operating room (OR) and when using video playback during post-operative review in obstetrics and gynecology (OBGYN) training.